2019
DOI: 10.1002/chem.201903562
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of a Novel Copper‐Dependent Intermediate in a Lytic Polysaccharide Monooxygenase

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are copper‐containing enzymes capable of oxidizing crystalline cellulose which have large practical application in the process of refining biomass. The catalytic mechanism of LPMOs still remains debated despite several proposed reaction mechanisms. Here, we report a long‐lived intermediate (t1/2=6–8 minutes) observed in an LPMO from Thermoascus aurantiacus (TaLPMO9A). The intermediate with a strong absorption around 420 nm is formed when reduced LPMO‐CuI reacts with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(100 citation statements)
references
References 70 publications
7
91
2
Order By: Relevance
“…Moreover, the reversibility of the two reactions are different: in case of TaLPMO9A the process is reversible while in case of LsAA9 the process is irreversible. 34,35 Finally, the two studies suggest different roles in the mechanism of the observed intermediates.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, the reversibility of the two reactions are different: in case of TaLPMO9A the process is reversible while in case of LsAA9 the process is irreversible. 34,35 Finally, the two studies suggest different roles in the mechanism of the observed intermediates.…”
Section: Introductionmentioning
confidence: 94%
“…Yet, until very recently, this tyrosine has not been proposed to be directly involved in the mechanism [19][20][21][22] . However, two recent experimental studies have (in absence of substrate) managed to trap and spectroscopically characterize an intermediate, presumably involving a deprotonated tyrosine 34,35 . Both studies obtain well-defined optical spectra by adding H2O2 and an electron donor (ascorbate) to an AA9 LPMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether the higher photostability of the WSCP-Chl a would lead to higher TtAA9 product formation, light-driven activity assays were performed with TtAA9 using varying concentrations of reductant. Since high concentrations of H 2 O 2 can be detrimental to LPMO activity 18,40 , and the WSCP was shown to be more stable at lower light intensities (Fig. 1b), the light intensity was reduced to 100 µmol m − 2 s − 1 for TtAA9 experiments.…”
Section: Light-driven Tt Aa9 Activity Assaysmentioning
confidence: 99%
“…The cosubstrates interact with a reduced copper active site forming a reactive intermediate which can then oxidize the substrate. Recent studies have demonstrated signi cantly higher product yields when H 2 O 2 is involved in LPMO catalysis 18,19 . However, the amount of H 2 O 2 has to be controlled as high concentrations have been shown to be detrimental to LPMO activity 17 .…”
Section: Introductionmentioning
confidence: 99%